Sign language translation: a system development to translate Malay language to Malaysian sign language / Mohd Zahir Radzali - Radzali, Mohd Zahir (2008)
Sign Language Translation System is widely been developed and research by many organization, individuals and universities. Sign Language Translation System is very useful system that can provide sources of learning sign language that can be used by many people. This Sign Language Translation System is translate Malay Language to Malaysian Sign Language (MySL)